Search for single-top production in ep collisions at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Aushev, V; Aushev, Y; Bachynska, O; et al. (2012)
A search for single-top production, ep→etX, has been performed with the ZEUS detector at HERA using data corresponding to an integrated luminosity of 0.37 fb -1. No evidence for top production was found, consistent with the expectation from the Standard Model. Limits were computed for single-top production via flavour changing neutral current transitions involving a neutral electroweak vector boson, γ or Z. The result was combined with a previous ZEUS result yielding a total luminosity of 0.50 fb -1. A 95% credibility level upper limit of 0.13 pb was obtained for the cross section at the centre-of-mass energy of √s=315 GeV. © 2012 Elsevier B.V.